2019
DOI: 10.1007/s11906-019-0911-5
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of Renal Microcirculation Regulation: Connecting Tubule-Glomerular Feedback

Abstract: Purpose of Review-In this review, we summarized the current knowledge of connecting tubule-glomerular feedback (CTGF), a novel mechanism of renal microcirculation regulation that integrates sodium handling in the connecting tubule (CNT) with kidney hemodynamics.Recent Findings-Connecting tubule-glomerular feedback is a crosstalk communication between the CNT and the afferent arteriole (Af-Art), initiated by sodium chloride through the epithelial sodium channel (ENaC). High sodium in the CNT induces Af-Art vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…The autoregulation of RBF is mediated primarily by two mechanisms, the fast myogenic response and the slower macula densa (MD) tubulo-glomerular feedback (TGF). Two other autoregulatory mechanisms have been proposed, one that operates at a low frequency [ 6 ] and one that involves crosstalk between the connecting tubule and the afferent arteriole [ 7 ], but their contributions appear smaller and they remain poorly understood [ 8 ]. Modeling studies have significantly expanded our understanding of these intrinsic regulatory mechanisms, including their relative contributions and interactions and how they are affected by specific pathological conditions [ 9 , 10 ].…”
Section: Renal Blood Flowmentioning
confidence: 99%
“…The autoregulation of RBF is mediated primarily by two mechanisms, the fast myogenic response and the slower macula densa (MD) tubulo-glomerular feedback (TGF). Two other autoregulatory mechanisms have been proposed, one that operates at a low frequency [ 6 ] and one that involves crosstalk between the connecting tubule and the afferent arteriole [ 7 ], but their contributions appear smaller and they remain poorly understood [ 8 ]. Modeling studies have significantly expanded our understanding of these intrinsic regulatory mechanisms, including their relative contributions and interactions and how they are affected by specific pathological conditions [ 9 , 10 ].…”
Section: Renal Blood Flowmentioning
confidence: 99%
“…CTGF has recently been suggested as a novel mechanism for renal microcirculatory regulation that involves sodium handling in the connecting tubules (CNT) [ 28 ]. It has been shown that a high sodium content in CNT could cause Af-Art vasodilation initiated by activation of epithelial Na + channel in a distal nephrons [ 16 , 29 ].…”
Section: Autoregulation Of the Kidney Microcirculationmentioning
confidence: 99%
“…Los derivados del ácido araquidónico inducen una respuesta vasodilatadora en el endotelio al bloquear la ON sintasa y la ciclooxigenasa (Cox). Por lo cual, el ON junto al ácido araquidónico participan en la modulación de la actividad del mecanismo de RTG (Burke y cols., 2014;Ren y cols., 2009;Romero y Carretero, 2019b, 2019aH. Wang y cols., 2010).…”
unclassified